Arsitektur Berkelanjutan Pada Masjid yang Dibangun Yayasan Amalbakti Muslim Pancasila (YAMP) - Ripqi, Muhammad; Rahman, Akbar; Febrita, Yuswinda (Nusantara Journal of Science and Technology, 2025)
This study analyzes the application of sustainable architectural principles in mosques built by Yayasan Amalbakti Muslim Pancasila (YAMP), an institution that has played a significant role in the development of national mosques with standardized prototypes. Using a descriptive qualitative approach through literature review, observation, and documentation, this research examines how sustainability principles are applied. The analysis shows that although these principles are not explicitly formulated in the design documents, YAMP mosques inherently contain sustainable potential. This is evident in the efficient use of land, thermal comfort, adequate access to water, the use of durable and efficient materials, and the function of the mosque as a center for social, cultural, and economic activities. The distinctive three-tiered roof design also represents the preservation of Nusantara architectural culture. These findings affirm that the YAMP mosque prototype can be regarded as an example of sustainable architecture implementation in Indonesia.